2001
DOI: 10.1111/j.2042-7174.2001.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

European barriers to the implementation of pharmaceutical care

Abstract: Objective — To establish the perceived barriers to the implementation of pharmaceutical care into community pharmacy practice in different European countries and the relative importance of these barriers. Method — Structured interviews with representatives from national pharmacists' organisations or pharmaceutical care researchers from 11 European countries known to be actively attempting to implement pharmaceutical care. Respondents were asked to consider a list of 25 potential barriers to pharmaceutical care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 1 publication
(1 reference statement)
4
31
0
Order By: Relevance
“…The results of the present study were compatible with European barriers to the implementation of pharmaceutical care [15] in their findings of lack time and trained staff. Moreover their findings showed that lack of remuneration has great effect in the progression of the practice.…”
Section: Discousion and Conclusionsupporting
confidence: 78%
See 2 more Smart Citations
“…The results of the present study were compatible with European barriers to the implementation of pharmaceutical care [15] in their findings of lack time and trained staff. Moreover their findings showed that lack of remuneration has great effect in the progression of the practice.…”
Section: Discousion and Conclusionsupporting
confidence: 78%
“…Moreover their findings showed that lack of remuneration has great effect in the progression of the practice. Lack of pharmacists' time was also identified in many other studies [15,17,21,22] as the major barrier limiting pharmacists' provision of advance health services. However, other studies findings showed some differences.…”
Section: Discousion and Conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…[20] They expressed a willingness to implement pharmaceutical care practice but identified a number of barriers for successful implementation. [21][22][23] When addressing inter/intra professional relationships activities, this study received the lowest scores and seem to be of least concerned by pharmacists among all professional activities. The results reflect the existence of some barriers to establishing such relationships in practice in the community setting.…”
Section: Discussionmentioning
confidence: 99%
“…The causes for this have long been discussed within the profession and the reasons range from the lack of payment for these services to the professional inertia regarding the adoption of new forms of practice [50, 51]. Also, another barrier commonly cited has been the “lack of time” reported by pharmacists [52, 53]. Analyzing our results, there seems to exist a perception gap about pharmacists’ free time.…”
Section: Discussionmentioning
confidence: 76%